Livelihood Vulnerability of Small-scale Fisher Households to Climatic Hazards: A Gendered Analysis in the South West Coast of India - Natarajan, Aswathy; Zacharia, P. U.; Salim, Shyam S.; Athira, N. R.; Sunil, P. V. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during January–March, 2021 at Ernakulam district of Kerala state, India to study the livelihood vulnerability of small-scale coastal fisher households to climatic hazards in a gendered perspective. The state of Kerala along the south west coast of India has been identified as one of the climate vulnerable hotspots threatened by extreme events including sea level rise. Coastal fisher communities across the world are highly vulnerable to climate change in view of the dependence on fishery-based livelihoods, depletion of marine resources, low resource possession, lack of fishing rights and other environmental hazards. Considering the low resilience of women to climate change, gender-based livelihood vulnerability assessments are essential for effective decisions on adaptation strategies within the constraints of local resources and infrastructure. The paper depicts the results of the gendered vulnerability assessment of small-scale fisher households in Ernakulum district of Kerala state. A composite livelihood vulnerability index (LVI) was developed based on the data on 400 small scale fisher households. The LVI was constructed across 8 major components consisting of socio-demographic particulars, health, water, food, natural and physical capital, financial capital, social capital and climate hazards. The results indicated that female- headed households had higher vulnerability (LVI-0.40) compared to male -headed households (LVI-0.37) and suggest the need for gender inclusive approach in the national, state and local level action plans on climate change adaptation and disaster-risk reduction programme.